Online speech and offline violence: Reflections on the current violence in Ethiopia (Global Media Journal - German Edition, 2023)
Drawing on the author’s keynote at the Forum Media and Development (fome) in 2021, this article explores some of the assumptions between social media content and offline violence, particularly in Africa, and with special reference to the ongoing conflict in Ethiopia. As with previous studies on radio and violence, much of the current debate about social media has been driven by simplistic models of behaviour that attribute little or no agency to the communities and individuals involved, and minimize the contexts, including the history, in which the violence is occurring. While there are very real concerns about the failure of BigTech to moderate online content particularly in African markets which are peripheral to their profit models, there is an urgent need for a more nuanced approach to understanding the significant variance as to how communities interpret and respond to information they receive from different actors, and on very different mediums, in situations of violent conflict.
Keywords: social media; conflict; Africa; media effects; peace